Implementasi kaidah “Adh-dhararu Yuzal” dalam kebijakan pendidikan modern - Khotimah, Siti (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze the application of the “Adh-dhararu Yuzal” rule in modern education policy. The research method used is a qualitative approach with literature study and analysis of relevant education policies. The results show that the principle of “Adh-dhararu Yuzal” which means that harm must be eliminated, is effective in overcoming problems in education policy such as inequality of access, psychological pressure on students, and preparedness for crisis situations as well as examples and challenges in its implementation. This research concludes that the application of this principle can support education policies that are responsive, inclusive and sustainable, with an emphasis on student welfare and the elimination of negative impacts. This confirms that the application of this principle is relevant to maintaining sustainability and safety in modern education.